Optimizing the Performance of the Visual P300-Speller Through Active Mental Tasks Based on Color Distinction and Modulation of Task Difficulty - Li, Qi; Lu, Zhaohua; Gao, Ning; Yang, Jingjing (Frontiers in Human Neuroscience, 2019)
Objective: P300-speller is the most commonly used brain-computer interface for providing a means of communication to patients with amyotrophic lateral sclerosis. However, the performance of the P300-speller brain-computer interface is still inadequate. We investigated whether the performance of P300-speller can be further improved by increasing the mental effort required of the user. Methods: We designed two active mental tasks for a P300-speller based on a differently colored smiling cartoon-face paradigm. The tasks were based on color distinction, and their difficulty was modulated. One of the active mental tasks (DC task) required participants to focus on and distinguish the color of a target, while the other task (CN+DC task) required participants to simultaneously count the number of times a target flashed and distinguish its color. Results: The amplitudes of the event-related potentials in both DC and CN+DC tasks were higher than that in the CN task. The significant difference in the amplitudes between the DC and CN tasks was observed around the parietal-central area from 440 ms to 800 ms (late positive component), and that between the CN+DC and CN tasks was observed around the left-frontal and right-frontal areas from 320 ms to 480 ms (P3a) and the parietal-central area from 480 ms to 800 ms (P3b and late positive component). The latency of the P300 potential in the CN+DC task was significantly longer than that in the CN task at F3, Fz, F4, C4, Pz, and P4 (P<0.05). Offline (P<0.05 at superposing once, twice, and thrice) and online (P<0.001) classification results showed that the average accuracies in the CN+DC task were significantly greater than that in the CN task. Similar results were found for online information transfer rates (P<0.001). In addition, we found that the average online accuracies in the DC task were greater than those in the CN task, although the difference was not statistically significant (P=0.051). Significance: The active mental task based on task difficulty modulation can significantly improve the performance of the P300-speller, and that based on color distinction shows a trend of improved performance.